Pediatric thyroid surgery: Retrospective analysis on the first 25 pediatric thyroidectomies performed in a reference center for adult thyroid diseases - Quaglino, Francesco; Bellocchia, Alex Bruno; Tuli, Gerdi; Munarin, Jessica; Matarazzo, Patrizia; Cestino, Luca; Festa, Federico; Carbonaro, Giulia; Oleandri, Salvatore; Manini, Claudia; Vergano, Riccardo; De Sanctis, Luisa (Frontiers in Endocrinology, 2023)
Introduction. Pediatric thyroid carcinoma represents about 4-5% of all pediatric carcinoma with an incidence of 0.5 cases /100,000, compared to 2-10/100000 cases in adults. The aim of this study is to present the experience of a reference adult endocrine surgery unit in charge of the treatment of pediatric thyroid diseases. Materials and methods. From January 2019 to September 2022, 25 patients, aged 5-17, underwent thyroid surgery. We analysed indications for surgery, use of intraoperative nerve monitoring (IONM), definitive histological examination, postoperative outcomes and risk factors related. Results. Surgical indication was performed for Graves' disease (27%) and for nodular pathology (73%): of these, four were malignant lesions (TIR4 / TIR5), eight with indeterminate characteristics (TIR3A / TIR3B) and four characterized as benign (TIR1 / TIR2). Total thyroidectomy (TT) was performed in 76% of cases, three of which were prophylactic for the activation of RET gene mutation in MEN 2A. IONM was used in eight cases (32%), all patients aged 11 years or less. FNA’s accuracy was 100% for lesions typified as benign and malignant (TIR1/TIR2 and TIR4/TIR5). The overall malignancy rate achieved was 40% and in the final histological examination 75% of the TIR 3B lesions were malignant. Six patients (24%) developed hypoparathyroidism in the first postoperative day, with normalization of calcium values within thirty days in 5 patients. Conclusions. Pediatric thyroid nodules are rare and distinguished from adult thyroid disease by a worse prognosis and higher malignancy rates. Our work reports a much higher malignancy rate among indeterminate TIR 3B lesions than observed in the adult population and the three patients who underwent prophylactic total thyroidectomy for activating RET gene mutation had all a definitive histological diagnosis of medullary carcinoma. Post-surgical hypoparathyroidism is a common finding in these patients: in most cases the condition is transient and it benefits from supportive therapy. Intraoperative finding of a thinner recurrent laryngeal nerve in younger patients makes nerve isolation more difficult than in adult surgery: IONM is recommended in patients under 12. Pediatric thyroid surgery is challenging, we sustain it requires referral thyroid Centers for thyroid disease with highly skilled general endocrine surgeons.